COMPUTER SIMULATION INVESTIGATION OF CRASH BOX DESIGN AS SAFETY-PROTECTION TECHNOLOGY FOR INDONESIA HIGH SPEED TRAIN - Musyaffa, Dzikri Amali; Choiron, Moch. Agus; Irawan, Yudy Surya; Hidayati, Nafisah Arina; Taryono, Taryono (International Journal of Mechanical Engineering Technologies and Applications, 2023)
The crashworthiness of a railway vehicle has been developed to provide energy absorption capacity and efficiency of energy absorption. This study presents a computer simulation to determine the energy-absorbing structure of the new addition of a crash box design on the Indonesian high-speed train in a collision scenario. The crashworthiness analysis in the crash box is done with software based on finite element methods. The crash box is modeled as a thin-walled structure located in coupler housing, between the draft gear and the car frame. The test model was carried out according to the 2019 SNI 8826 standard using a frontal impact test with an impactor mass of 38.807 kg and a speed of 10 m/s. The pattern of deformation and energy absorption is obtained by calculating the area under the graphical curve of the relationship between the force reaction and the displacement obtained from the simulation. The deceleration of the train is obtained from the graph of acceleration against time on the impactor. The simulation results show that the addition of a crash box design as an energy absorption module on a safety protection technology for railway vehicles can reduce the severity of the impact and improve passenger safety. The application of the initial crash box model also shows an unacceptable train deceleration in the SNI 8826 test standard.